2014
DOI: 10.1186/1477-7827-12-71
|View full text |Cite
|
Sign up to set email alerts
|

The importance of the one carbon cycle nutritional support in human male fertility: a preliminary clinical report

Abstract: BackgroundSperm chromatin structure is often impaired; mainly due to oxidative damage. Antioxidant treatments do not consistently produce fertility improvements and, when given at high doses, they might block essential oxidative processes such as chromatin compaction. This study was intended to assess the effect on male sub-fertility of a pure one carbon cycle nutritional support without strong antioxidants.MethodsMale partners of couples resistant to at least 2 assisted reproductive technology (ART) attempts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 36 publications
2
43
0
1
Order By: Relevance
“…Indeed betalaines have the property to stratify on plasma membranes where they act as suicide oxidation substrates to prevent the trigger of the lipoperoxidative cascade so to further aid sperm motility. This nutritional intervention was tested in male [44–46] and female [46] partners in couples with previous IVF/ICSI failures willing to undergo another ART attempt. These studies included couples with at least 2 previous ART failures and with a male partner showing sperm DNA Fragmentation Index (DFI—Measure of oxidative molecular damage, as assessed by TUNEL) and/or a Sperm nuclear Decondensation Index (SDI—Measure of integrity of chromatin tertiary structure, as assessed by aniline blue staining) > 20 % irrespective of the other sperm parameters.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed betalaines have the property to stratify on plasma membranes where they act as suicide oxidation substrates to prevent the trigger of the lipoperoxidative cascade so to further aid sperm motility. This nutritional intervention was tested in male [44–46] and female [46] partners in couples with previous IVF/ICSI failures willing to undergo another ART attempt. These studies included couples with at least 2 previous ART failures and with a male partner showing sperm DNA Fragmentation Index (DFI—Measure of oxidative molecular damage, as assessed by TUNEL) and/or a Sperm nuclear Decondensation Index (SDI—Measure of integrity of chromatin tertiary structure, as assessed by aniline blue staining) > 20 % irrespective of the other sperm parameters.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 84 patients fulfilled the entry criteria of this non comparative study [44], in 28 cases (33 %) there was an associated female factor. For the first time ever, both sperm indexes significantly improved (DFI from 29.7 to 23.1 %, p  < 0.001; SDI from 40.1 to 36.3 %, p  < 0.001) confirming that the new support strategy is effective in counteracting oxidative damage without negatively influencing (reductive stress) the nuclear decondensation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore measuring substrate abundance and enzyme activities related to the folate and methionine cycle are important indicators of possible disruptions in the methylation cycle. Indeed, several studies point toward beneficial effects of inducing a well‐balanced folate and methionine cycle in both males (Dattilo et al, ) and females (Haggarty et al, ; Boxmeer et al, ,; Gaskins et al, ; Murto et al, ) for pregnancy success in ART. Furthermore, a recent study in mouse blastocysts showed the necessity of folate and BHMT homocysteine recycling pathways to ensure that sufficient levels of S‐adenosylmethionine enable a sufficient DNA methylation level (Zhang et al, ).…”
Section: Robustness Of the Methylation Rate In The Face Of Systemic Fmentioning
confidence: 99%
“…Эти данные позволяют сделать заключение, что нарушение конденсации хроматина может служить предиктивным показателем аномалий развития эмбри-она как in vivo, так и in vitro. Причем негативные по-следствия нарушения компактизации проявляются в раннее время после оплодотворения [77], приводя к раннему эмбриональному аресту [78] и спонтанным абортам [27,79].…”
Section: корреляционная электронная микроскопияunclassified